SPIRITUAL ENTREPRENEURSHIP: MENEMUKAN KEMBALI ETOS BISNIS NABI DALAM EKONOMI MODERN - Muhammad Zaki (Yayasan An-Nur Meunara Baro, 2025)
The phenomenon of ethical crisis and dehumanization in the global economy calls for a new paradigm that balances material and spiritual dimensions. This article aims to revisit the concept of spiritual entrepreneurship by exploring the business ethics of Prophet Muhammad SAW as the foundation of modern Islamic economic morality. Using a qualitative library research approach, this study analyzes the relevance of Prophetic values such as honesty, trustworthiness, justice, and social responsibility within contemporary business contexts. The findings reveal that spiritual entrepreneurship is not merely a normative ethical framework but also a strategic management system that enhances trust, loyalty, and business sustainability. The integration between spirituality and professionalism establishes an entrepreneurial paradigm that perceives business as a form of worship rather than a mere economic pursuit. Moreover, spiritual values prove to be an effective solution to the moral crisis and social inequality generated by modern capitalism. By emulating the business ethos of the Prophet, Muslim entrepreneurs can create harmony between economic achievement and humanitarian responsibility. Thus, spiritual entrepreneurship serves as a vital foundation for developing an inclusive, just, and sustainable Islamic economy in the era of globalization.